Evaluation of outcomes in renal transplantation with hypothermic machine perfusion for the preservation of kidneys from expanded criteria donors. Issue 5 (10th April 2019) - Savoye, Emilie; Macher, Marie‐Alice; Videcoq, Michel; Gatault, Philippe; Hazzan, Marc; Abboud, Imad; Thierry, Antoine; Bertrand, Dominique; Drouin, Sarah; Sayegh, Johnny; Barrou, Benoit; Badet, Lionel; et al.
Abstract: In 2012, an expert working group from the French Transplant Health Authority recommended the use of hypothermic machine perfusion (HMP) to improve kidney preservation and transplant outcomes from expanded criteria donors, deceased after brain death. This study compares HMP and cold storage (CS) effects on delayed graft function (DGF) and transplant outcomes. We identified 4, 316 kidney transplants from expanded criteria donors (2011‐2014) in France through the French Transplant Registry. DGF occurrence was analyzed with a logistic regression, excluding preemptive transplants. One‐year graft failure was analyzed with a Cox regression. A subpopulation of 66 paired kidneys was identified: one preserved by HMP and the other by CS from the same donor. Kidneys preserved by HMP (801) vs CS (3515) were associated with more frequent recipient comorbidities and older donors and recipients. HMP had a protective effect against DGF (24% in HMP group and 38% in CS group, OR = 0.49 [0.40‐0.60]). Results were similar in the paired kidneys (OR = 0.23 [0.04‐0.57]). HMP use decreased risk for 1‐year graft failure (HR = 0.77 [0.60‐0.99]). Initial hospital stays were shorter in the HMP group ( P < 0.001). Our results confirm the reduction in DGF occurrence among expanded criteria donors kidneys preserved by HMP.